Internal Models-Based Capital Regulation and Bank Risk-Taking Incentives - Kupiec, Paul (IMF Working Papers; Working Paper ;, 2002)
Advocates for internal model-based capital regulation argue that this approach will reduce costs and remove distortions that are created by rules-based capital regulations. These claims are examined using a Merton-style model of deposit insurance. Analysis shows that internal model-based capital estimates are biased by safety-net-generated funding subsidies that convey to bank shareholders when market and credit risk regulatory capital requirements are set using bank internal model estimates. These subsidies are not uniform across the risk spectrum, and, as a consequence, internal model regulatory capital requirements will cause distortions in bank lending behavior.